Point-scoring plays related to level of set win and in-game role during volleyball rules testing - Stankovic, M.; Ruiz-Llamas, G.; Peric, D.; Quiroga-Escudero, M. E. (Journal of Human Sport & Exercise, 2019)
The aim of this study was to analyse the characteristics of point-scoring plays related to level of set win and in-game role under experimental rules tested at the U23 Men`s Volleyball World Championship in Uberlandia, Brazil (21-point set, 15 seconds between points) from the 16th point in the first four sets and the 10th point in the fifth set. The analysis of 1335 points from 123 sets in 36 matches played by 144 males (average age 21.1±1.4 years) focused on in-game role (setter, outside hitter, middle blocker, opposite, libero), final score, finishing point actions (serve-ace, three attack types, three counter attack types, block), set outcome (Win-Lose), and level of set win (Walkover-Balanced-Tough). Pearson`s Chi-Square test was used for data analysis. The results showed that the difference in the structure of won and lost points decreased from walkover to balanced to tough sets. Attack-spike and block were the most frequently executed technical elements. Outside-hitter was identified as the in-game role that finished more points, followed by Opposite and Middle blockers. If the tested rules are applied, developing the block, serve and attacks may have greater influence on set outcome in the future.